2021
DOI: 10.1177/2309499021992605
|View full text |Cite
|
Sign up to set email alerts
|

Association between pre-operative anxiety and/or depression and outcomes following total hip or knee arthroplasty

Abstract: Purpose: While elective primary total hip (THA) and knee (TKA) arthroplasty are effective procedures for addressing the symptoms associated with advanced osteoarthritis, there is evidence to suggest that patient anxiety and depression are linked to poorer outcomes following surgery. Methods: A secondary analysis of prospectively-collected data of people undergoing primary elective THA or TKA for osteoarthritis across 19 hospitals was performed. We assessed outcomes at 1 year post-surgery for people with and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…This may be due to the low awareness rates, diagnostic rates, and treatment rates of mental disorders in Chinese patients [ 22 ]. Additionally, we found that a higher proportion of women were present in the distressed group than in the non-distressed group, which was similar to that in previous studies [ 23 , 24 ]. However, the proportion of women was relatively high in our study; the reason for that remains unknown and further investigation may be needed.…”
Section: Discussionsupporting
confidence: 91%
“…This may be due to the low awareness rates, diagnostic rates, and treatment rates of mental disorders in Chinese patients [ 22 ]. Additionally, we found that a higher proportion of women were present in the distressed group than in the non-distressed group, which was similar to that in previous studies [ 23 , 24 ]. However, the proportion of women was relatively high in our study; the reason for that remains unknown and further investigation may be needed.…”
Section: Discussionsupporting
confidence: 91%
“…The authors concluded that patients should be treated for depressive symptoms pre-and postoperatively to maximize THA outcomes. The results of this study are similar to those of the present study, despite the use of a different categorization approach for mental health conditions [33]. The strength of utilizing psychiatrist-diagnosed patients instead of a self-scored questionnaire such as the GDS would be the precision and accuracy of medical diagnosis.…”
Section: Depression and Tha Outcomessupporting
confidence: 84%
“…Seagrave et al explored the association between depression (diagnosed by a psychiatrist) treated with medication and outcomes of THA one year postoperatively [33]. Anxiety and depression groups experienced a greater improvement in the Oxford Hip Score, while there was a less global joint improvement, and they were more likely to have major complications.…”
Section: Depression and Tha Outcomesmentioning
confidence: 99%
“…Also, our study found an association between antidepressant use prior to primary surgery and increased risk of revision; however, we did not find that patient levels of anxiety and depression recorded in preoperative PROMS were a risk factor. In another study of hip and knee replacement, use of antidepressant medication preoperatively did not affect outcomes 1 year postsurgery, 31 but the effect on mid-late term revision was not discussed.…”
Section: Discussionmentioning
confidence: 97%